Exploring the Impact of Didactic Dubbing on Speaking Skills and Motivation in English for Specific Purposes Settings - Buil Beltrán, Paula (Journal of Audiovisual Translation, 2024)
The field of Didactic Audiovisual Translation (DAT) is witnessing significant expansion, with growing research emphasis on areas such as listening skills, vocabulary acquisition, and intonation. Despite this, research within the domain of English for Specific Purposes (ESP) concerning DAT is still relatively scarce. This is noteworthy considering its potential to address the specific needs of ESP learners, including preparing for common challenges like job interviews, particularly among Spanish students learning a foreign language. This paper aims to address ESP students’ needs through a mixed-method approach that analyses the responses of 95 ESP students in the School of Engineering and Architecture at the University of Zaragoza who completed a lesson plan on job interviews during the 2021/2022 academic year. These lesson plans were designed for practical sessions within the Technical English course to improve students’ speaking skills. To compare their effectiveness, students were divided into two groups: an experimental group (EG) using a DAT-based plan and a control group (CG) with a traditional curriculum. The study suggests that dubbing and traditional methods are effective while demonstrating that the continuous use of dubbing in the classroom would enhance speaking skills more effectively than traditional methods. Moreover, students perceive dubbing as beneficial for English oral skills, indicating high engagement with DAT in class, highlighting its potential for language learning. Lay summary Didactic audiovisual translation (DAT) is a fast-growing and unstoppable field, experiencing its apogee, with more research focusing on a wide range of aspects such as listening skills, vocabulary acquisition or intonation (Ávila-Cabrera & Rodríguez-Arancón, 2021; Bolaños García-Escribano et al., 2021; Couto-Cantero et al., 2021; Talaván & Lertola, 2022). Despite this, there is still an unexplored field that can benefit enormously from this methodology, English for Specific Purposes (ESP). Nowadays, research on DAT in ESP (Talaván, 2006; Ávila-Cabrera, 2021) is relatively scarce, and there is still untapped potential for its use in ESP teaching. Moreover, scholars such as Nunan (2004) and Català-Hall (2013) highlight the urgency of creating specific programmes that address the immediate needs that some learners may have while studying ESP. One of these necessities required by ESP students is the ability to learn how to hold and successfully pass a job interview. However, to do it, students need to master the topic while they foster their speaking skills, which is one of the Spanish students' handicaps while learning a foreign language (FL). This paper seeks to solve these ESP students’ necessities by creating and implementing two lesson plans in the School of Engineering and Architecture at the University of Zaragoza; in the academic year 2021/2022, based on Job Interviews. The lesson plans were designed for being carried out in the practical sessions of the subject Technical English, a transversal elective course, to enhance students speaking skills. In order to make a comparative analysis, students were divided into two, an experimental group (EG) that counted with a lesson plan based on DAT and a control group (CG) that had a lesson plan based on traditional methodologies. The lesson aim was that, in the end, students were able to develop and express themselves in a professional situation like doing a job interview; thus, the lessons try to foster ESP students’ production skills within a communicative framework. This paper presents, then, the methodology and the instruments used for the creation and implementation of the study together with an in-deep analysis in which quantitative and qualitative data are analysed. First, in each lesson, students had to complete a final task to obtain a mark of up to five points that were assessed by means of specific rubrics and compared among groups. The CG practical task was a role play, while the EG had a task of creative English dubbing. Then, students’ final perceptions obtained from a post-questionnaire are analysed, and a comparison among groups is made to see which group obtained the best results in their oral production skill development and which group felt more motivated throughout the lesson. This will lead us to the conclusion in which the strengths of this novel and creative methodology are highlighted by the analysis of the results obtained in each method and a comparison of the results from CG and EG.